2017
DOI: 10.5114/pg.2017.65677
|View full text |Cite
|
Sign up to set email alerts
|

Allergic enteritis in children

Abstract: The gastrointestinal form of food allergy is very common in children. The most frequently observed types are allergic proctitis and proctocolitis. In most cases the symptoms subside within the first 2 months of life. The babies seem healthy, and the only abnormality is a small amount of blood in stool. Symptoms can also include small intestine inflammation and colitis. Patients may present with irritability, abdominal pain, flatulence, colic, postprandial vomiting, chronic diarrhoea, and hindered physical deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…There is increasing evidence that neutrophils play an important role in the pathogenesis of allergic inflammation by mediating direct tissue injury or by releasing pro-inflammatory mediators 40 . Increased neutrophil numbers have also been detected in AE patients 5 . The potential of CCR8 antagonists has been considered to treat allergic asthma, since several studies have shown a role for CCR8 in the recruitment of Th2 cells and in the development of inflammation in murine models of allergic asthma 22,29,41 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is increasing evidence that neutrophils play an important role in the pathogenesis of allergic inflammation by mediating direct tissue injury or by releasing pro-inflammatory mediators 40 . Increased neutrophil numbers have also been detected in AE patients 5 . The potential of CCR8 antagonists has been considered to treat allergic asthma, since several studies have shown a role for CCR8 in the recruitment of Th2 cells and in the development of inflammation in murine models of allergic asthma 22,29,41 .…”
Section: Discussionmentioning
confidence: 94%
“…Food allergy causes clinical symptoms systemically and/or locally in cutaneous, respiratory, ocular, and gastrointestinal tissues 13 . Gastrointestinal forms of food allergy, which include allergic enteritis and colitis, are observed most frequently in pediatric patients with cow’s milk, or soy allergy, and also in adult patients allergic to other foods, including eggs of hens and wheat 4,5 . Biopsies have shown varying degrees of villous atrophy, tissue edema, crypt abscess formation, and eosinophil infiltration in the inflamed tissues of patients with allergic enteritis and colitis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, Allergic enteritis (AE) is a gastrointestinal form of food allergy. 1 Compared with other clinical phenotypes of allergy, the pathomechanisms of AE have not been elucidated. In this study, we provide evidence, based on the studies of two mast cell-deficient mouse strains (KIT (W−sh/W−sh) bearing the W-sash (W(sh)) inversion is produced by innate lymphoid cells (ILC)2, supporting their capacity to protect against helminthic infections in the intestines.…”
Section: Mast Cells Partly Contribute To Allergic Enteritis Developme...mentioning
confidence: 99%
“…FACS analysis showed that KIT W−sh/W−sh mice had reduced numbers of both eosinophils (CD45 + CD11b + SiglecF + cells) and neutrophils (CD45 + CD11b + SiglecF − Ly6G + cells), whereas Cpa3 Cre/+ mice had reduced eosinophils, but not neutrophils, in intestinal tissues (Figures2A and S2A-B).The W-sh mutation broadly affects c-Kit expression in myeloid precursor cells and increases granulocytic myeloid-derived suppressor cells, 2 which may contribute to reduced neutrophil accumulation and inflammation in KIT W−sh/W−sh mice. Importantly, both mast cells and eosinophils are observed in biopsy specimens upon microscopic inspection in most patients with AE 1. Yagi et al3 showed that the presence of neutrophils in intestinal biopsies is an indicator of a severe course of AE.…”
mentioning
confidence: 99%
“…Gross rectal bleeding should resolve within 72–96 h, but the total resolution of symptoms takes 1–2 weeks from the beginning of the diet. 6 …”
Section: Introductionmentioning
confidence: 99%